Public Health Expenditures and Clinical and Social Complexity of Tuberculosis Cases–Alameda County, California, July-December 2017. Issue 2 (March 2022) - Shiau, Rita; Holmen, Jenna; Chitnis, Amit S.
Abstract : Context: Alameda County, California, is a high tuberculosis (TB) burden county that reported a TB incidence rate of 8.1 per 100 000 during 2017. It is the only high TB burden California county that does not have a public health–funded TB clinic. Objective: To describe TB public health expenditures and clinical and social complexities of TB case-patients. Design, Setting, and Participants: Public health surveillance of confirmed and possible TB case-patients reported to Alameda County Public Health Department during July 1, 2017, to December 31, 2017. Social complexity status was categorized for all case-patients using surveillance data; clinical complexity status, either by surveillance definition or by the Charlson Comorbidity Index (CCI), was categorized only for confirmed TB case-patients. Main Outcome Measures: Total public health and per patient expenditures were stratified by insurance status. Cohen's kappa assessed concordance between clinical complexity definitions. All comparisons were conducted using Fisher's exact or Kruskal-Wallis tests. Results: Of 81 case-patients reported, 68 (84%) had confirmed TB, 29 (36%) were socially complex, and 15 (19%) were uninsured. Total public health expenditures were 487 194, and 18% of expenditures were in nonlabor domains, 57% of which were for TB treatment, diagnostics, and insurance, with insured patients also incurring such expenditures. Median per patient expenditures were significantly higher for uninsured and government-insured patients than for privately insured patients (7007 and 5045 vs 3704; P = .03). Among confirmed TB case-patients, 72% were clinically complex by surveillance definition and 53% by the CCI; concordance between definitions was poor (κ = 0.25; 95% confidence interval, 0.03-0.46). Conclusions: Total public health expenditures approached 500 000. Most case-patients were clinically complex, and about 20% were uninsured. While expenditures were higher for uninsured case-patients, insured case-patients still incurred TB treatment, diagnostic, and insurance-related expenditures. State and local health departments may be able to use our expenditure estimates by insurance status and description of clinically complex TB case-patients to inform efforts to allocate and secure adequate funding.